The Influence Of Knowledge Management Capabilities On The Learning Organisation And The Moderating Effect Of It Infrastructure And Corporate Culture - Lim, Huck Khiam (2008)

(untitled)
Pengetahuan adalah suatu harta yang amat penting dalam ekonomi kini yang berdasarkan pengetahuan.